Prevalence of Shiga toxin-producing Escherichia coli, Salmonella, and Campylobacter species among diarrheal patients from three major hospitals in Ethiopia - Teshale, A.M.; Abegaz, W.E.; Azmeraye, B.M.; Degefaw, D.; LaPolt, D.; Bonger, Z.; Kalayu, A.A.; Tigabu, E.; Gazu, Lina; Yimer, G.; Abate, E.; Tsige, E.; et al. (2025)
Diarrheal illness remains a major global health challenge, causing millions of deaths annually. Non-typhoidal Salmonella (NTS), Shiga toxin-producing Escherichia coli (STEC), and Campylobacter species (CAMPY) significantly contribute to this burden. Given the limited information on these pathogens in Ethiopia, this study aimed to estimate their prevalence among diarrhea patients in Ethiopia and identify risk factors for infection. A cross-sectional study was conducted from October 2021 to November 2022 in three hospitals in Ethiopia (Addis Ababa, Gondar, and Harar). Sociodemographic characteristics, clinical signs and symptoms were collected from study participants using a structured questionnaire. Stool samples were tested for NTS, STEC, and CAMPY using standardized methods. The prevalence of targeted pathogens was estimated overall and by study sites. Univariable and multivariable logistic regression were used to identify associated factors. A total of 2,331 patients were enrolled. The overall prevalence of NTS, STEC (stx only), STEC (stx + eae), and CAMPY was 1.29% (95%CI: 0.91, 1.84), 12.56% (95%CI: 11.29, 13.98), 3.43% (95%CI: 2.77, 4.25), and 4.46% (95%CI: 4.61, 8.00), respectively. Harar had the highest prevalence of all the pathogens compared to Addis Ababa and Gondar. Odds of NTS in Harar were over 10 (AOR: 10.43: 95%CI: 2.95, 69.20) and 3.5 times (AOR: 3.57: 95%CI: 1.50, 9.90) higher than that in Addis Ababa and Gondar, respectively. Odds of STEC (stx only) in the dry (AOR: 1.97: 95%CI: 1.37, 2.90) and long rainy (AOR: 1.80: 95%CI: 1.20, 2.69) seasons were nearly twice the odds in the short rainy season. Odds of CAMPY infection decreased by 3.29% (AOR: 0.97: 95%CI: 0.95, 0.98) with every one-year increase in age. Moreover, the odds of CAMPY infection for rural residents (AOR: 1.93, 95%CI: 1.15, 3.19) were nearly twice that of urban residents. This is the first study to estimate the prevalence of NTS, STEC, and CAMPY simultaneously across all age groups and diverse regions in Ethiopia, revealing significant variations. Results can be used to understand the burden of disease, inform clinical management and risk mitigation strategies to reduce illness in Ethiopia.